Gatekeepers in the health financing scheme: Assessment of knowledge, attitude, practices, and participation of Malaysian private general practitioners in the PeKa B40 scheme. - Mohammad Husni Jamal; Aznida Firzah Abdul Aziz; Azimatun Noor Aizuddin; Syed Mohamed Aljunid (PLoS ONE, 2023)
This is cross-sectional research done to assess the readiness of the private Malaysian general practitioners (GPs) for the implementation of the national health financing scheme. The study focused on their levels of knowledge and attitudes towards the types of health financing scheme, gatekeeper roles in the health financing scheme, and their participation in the PeKa B40 scheme. Their acceptance and level of participation in the national health financing scheme (NHFS) were also assessed. A set of self-designed and pre-tested questionnaires focusing on the aforementioned objectives were mailed to the respondents. The selection of respondents was done by stratified random sampling of the GPs in all 14 Malaysian states at both urban and rural levels. Out of a calculated number of 362 GPs targeted, 296 responses were received which represented a response rate of 81.7%. The respondents had a mean age of 50.7 years 165 (55.75%) were males and 131 (44.3%) were females. The rural respondents totalled 158 (53.4%) as compared to those from urban 138 (46.6%) areas. The outcomes observed were that GPs with PeKa B40 provider status, positive attitude towards health financing schemes, gatekeeper roles, and PeKa B40, were strongly associated with their acceptance and level of participation in the NHFS. The GPs possessed a positive attitude and were generally ready to participate in the NHFS, but the lower scores in knowledge levels would require definite education and training plans to further enhance their readiness. More incentives should be given to GPs to enrol as PeKa B40 providers. The results of this study should be strongly considered by the government in the efforts to engage the Malaysian private GPs in the forthcoming NHFS. Most importantly, the role of GPs as gatekeepers needed to be implemented, and the PeKa B40 scheme be greatly improved.